Physiological quality of wheat seeds produced in different municipalities in the north of the State of Paraná - Ortiz, Thiago Alberto (Revista de Ciências Agroveterinárias, 2024)
Due to the importance of triticulture for Brazilian agriculture, the study aimed to evaluate the physiological quality of wheat seeds produced in different municipalities in the north of the State of Paraná. The experiment was conducted at the Seed Laboratory of the State University of Londrina (UEL). The assay consisted of analyzing the physiological quality of wheat seeds cv. CD 116, produced in four municipalities in the state of Paraná (Rolândia, Cambé, Marilândia do Sul, and Ibiporã), in the 2011 cropping season, sampled at random in different cooperatives and seed-producing companies. The experiment was conducted in a completely randomized design and the physiological quality of the wheat seed batches was evaluated from the variables: first germination count and germination (germination test); viability (tetrazolium test); vigor (accelerated aging and cold tests); vigor, emergence speed index, and mean emergence time (seedling emergence test in the sand); shoot and seedling length, and shoot and seedling dry mass (seedling length test). The data were subjected to variance analysis and the means were compared using the Tukey test (p < 0.05). The municipality where the seeds were produced influenced the physiological quality of wheat seeds. In the present experiment, the production fields located in Rolândia and Cambé contributed to batches with greater germination and vigor. Therefore, the production environment is a factor that must be taken into consideration when planning the crop. The tetrazolium test, as well as the variables, mean emergence time, seedling length, and shoot dry mass, were not efficient in separating the batches according to physiological quality.